Exploring the outcomes of enterprise and entrepreneurship education in UK HEIs: An Excellence Framework perspective. Issue 3 (June 2023) - Bozward, David; Rogers-Draycott, Matthew; Smith, Kelly; Mave, Mokuba; Curtis, Vic; Aluthgama-Baduge, Chinthaka; Moon, Rob; Adams, Nigel
The purpose of this paper is to investigate data relating to the outcomes of enterprise and entrepreneurship education (EEE) activity in UK higher education institutions (HEIs). This is achieved via the use of data obtained from the Research Excellence Framework (REF), the Teaching Excellence and Student Outcomes Framework (TEF), the Knowledge Excellence Framework (KEF) and the Higher Education Business and Community Interaction (HE-BCI) survey. Overall, the analysis suggests, powerfully, that EEE impacts research, teaching and knowledge exchange in a variety of ways. Firstly, it shows that EEE, in terms of the REF, may be up to 46 times more impactful than other management disciplines. Secondly, with regard to TEF submissions, it highlights a positive relationship between the use of the EEE terms and the award level achieved. Finally, research also demonstrates a link between membership of certain HEI mission groups and improved KEF metrics when compared to the sector averages. There is a clear need to research how to develop successful EEE interventions and demonstrate their impact on the graduate, the university ecosystem and the wider economy. These data sources and methodology have not previously been used to develop a narrative for EEE across a university sector in the UK.